Are Tai Chi and Qigong effective in the treatment of traumatic brain injury? A systematic review - Nicole Alexandra Laskosky; Patricia Huston; Wai Ching Lam; Charlotte Anderson; Linda L. D. Zhong (BMC, 2024)
Abstract Background Traumatic brain injury (TBI) adversely affects both young and old and is a growing public health concern. The common functional, psychological, and cognitive changes associated with TBI and recent trends in its management, such as recommending sub-threshold aerobic activity, and multi-modal treatment strategies including vestibular rehabilitation, suggest that Tai Chi/Qigong could be beneficial for TBI. Tai Chi and Qigong are aerobic mind-body practices with known benefits for maintaining health and mitigating chronic disease. To date, no systematic review has been published assessing the safety and effectiveness of Tai Chi/Qigong for traumatic injury. Methods The following databases were searched: MEDLINE, CINAHL Cochrane Library, Embase, China National Knowledge Infrastructure Database, Wanfang Database, Chinese Scientific Journal Database, and Chinese Biomedical Literature Database. All people with mild, moderate, or severe TBI who were inpatients or outpatients were included. All Types of Tai Chi and Qigong, and all comparators, were included. All measured outcomes were included. A priori, we chose "return to usual activities" as the primary outcome measure as it was patient-oriented. Cochrane-based risk of bias assessments were conducted on all included trials. Quality of evidence was assessed using the grading of recommendation, assessment, development, and evaluation (GRADE) system. Results Five trials were assessed; three randomized controlled trials (RCTs) and two non-RCTs; only two trials were conducted in the last 5 years. No trial measured "return to normal activities" or vestibular status as an outcome. Four trials - two RCTs and two non-RCTS - all found Tai Chi improved functional, psychological and/or cognitive outcomes. One RCT had a low risk of bias and a high level of certainty; one had some concerns. One non-RCTs had a moderate risk of bias and the other a serious risk of bias. The one Qigong RCT found improved psychological outcomes. It had a low risk of bias and a moderate level of certainty. Only one trial reported on adverse events and found that none were experienced by either the exercise or control group. Conclusion Based on the consistent finding of benefit in the four Tai Chi trials, including one RCT that had a high level of certainty, there is a sufficient signal to merit conducting a large, high quality multi-centre trial on Tai Chi for TBI and test it against current trends in TBI management. Based on the one RCT on TBI and Qigong, an additional confirmatory RCT is indicated. Further research is indicated that reflects current management strategies and includes adverse event documentation in both the intervention and control groups. However, these findings suggest that, in addition to Tai Chi's known health promotion and chronic disease mitigation benefits, its use for the treatment of injury, such as TBI, is potentially a new frontier. Systematic review registration PROSPERO [ CRD42022364385 ].